A solution for designing and manufacturing signal normalization module for application in multichannel measurement system on military ship - Pham, Văn Hậu; Dinh, Van-Ngoc; Le, Anh Quang; Luong, Quốc Lệ (Journal of Military Science and Technology, 2022)
This article presents a solution to design a signal normalization module that can be used for many different types of sensors applied in multi-channel measurement systems on military ships. The results show that a signal normalization module using output signal normalization of many different sensors ensures high accuracy with an error of less than 0,6%. This solution helps save production costs and maintenance time in the work of securing high-tech weapons and equipment on military ships.